A Quasi Experimental Study to Assess the Effectiveness of Guidelines Regarding Knowledge of Parents on Care of Children with Leukemia in a Selected Hospital of Delhi - Gupta, Hina (Indian Journal of Nursing Sciences, 2024)
Aim: A quasi-experimental study to assess the effectiveness of guidelines regarding knowledge on the care of children with leukemia under age 19 years for the parents of children with leukemia. Methodology: Conceptual model used for the study was Orem’s supportive-educative system. Non-equivalent control group pre-test post-test design and convenient sampling technique was used in the study. The sample comprised 60 subjects taken from the Safdarjung Hospital with 30 subjects each in experimental and control groups. The experimental group was exposed to guidelines prepared. Results: After the administration of guidelines, the mean post-test (50.43) of the experimental group was higher than their mean pre-test knowledge score (25.86) with a mean difference of 24.57. t value of 18.47 for df (28) was found to be statistically significant at the 0.05 level as the table value for t was 2.05. This shows that the obtained mean difference of 24.57 was a true difference and not by chance. Thus, it can be inferred that the guidelines were found to be effective in enhancing the knowledge of parents. Conclusion: Hence, it is concluded that the guidelines prepared had a positive impact and was effective in improving the knowledge of subjects regarding the care of children with leukemia.